2019
DOI: 10.21608/edj.2019.72659
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Adaptation of a new Formulation of MTA Material used as Root-End Filling: A Scanning Electron Microscopy (SEM) Study

Abstract: Introduction Achieving a hermetic apical seal is mandatory to prevent ingress of any microorganisms or periapical fluids into the root canal system. Therefore it is essential to develop new materials having favorable physical, chemical and biological properties.Aim the purpose of this study was to use scanning electron microscopy to compare the marginal adaptation of new formulation of MTA (Harvard MTA), MTA flow and glass ionomer as root end filling materials using ultrasonic root-end preparation.Methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Only a single piece of research was found, evaluating the marginal adaptation of this cement at the same application site through scanning electron microscopy (SEM). El-Sherief et al [24] reported higher average gap size values with Harvard MTA (7.44 µm) at the interface than those observed in the MTA Flow group (3.95 µm). However, the presented statistical results were inconclusive regarding the significance of this difference.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Only a single piece of research was found, evaluating the marginal adaptation of this cement at the same application site through scanning electron microscopy (SEM). El-Sherief et al [24] reported higher average gap size values with Harvard MTA (7.44 µm) at the interface than those observed in the MTA Flow group (3.95 µm). However, the presented statistical results were inconclusive regarding the significance of this difference.…”
Section: Discussionmentioning
confidence: 86%
“…Only Jardine et al [27] reported a higher rate of porosity with Biodentine than MTA-Angelus. According to micro-CT investigations, Biodentine demonstrated a TPV% within a range of 2.48-6.66% and external porosity volume percentage (EPV) between 0.616-3.78%, and CPV% varied between 0.024-4.46% [23][24][25][26][27][28]. Only Toia et al [32] reported an unusually high porosity percentage of 50.45%, making this result difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…They measured the gap size between the root-end filling material and root canal wall in longitudinal sections using SEM, and found no significant difference among the three materials, although the gap size was the smallest in MTA and the largest in amalgam. El-Sherief et al [ 28 ] evaluated the marginal adaptation of glass ionomer, MTA Flow and a new formulation known as MTA Harvard as root-end filling materials using SEM. After 24 h, the gap size was significantly smaller in MTA Flow, indicating significantly superior marginal adaptation of MTA Flow compared with other tested materials.…”
Section: Discussionmentioning
confidence: 99%